The effectivity of emulgel from ethanolic extract of cocoa pod husk in mice model of painful diabetic neuropathy - Fifteen Aprila Fajrin; Didik Pudji Restanto; Lailatul Azkiyah; Yuli Witono; Melanny Ika Sulistyowaty (Journal of Advanced Pharmaceutical Technology & Research)
Painful diabetic neuropathy (PDN) is nerve damage caused by the accumulation of oxidative stress. Resveratrol, an antioxidant compound found in various plants, including cocoa pod husk, combats this condition. To prove the efficacy of an emulgel from an ethanolic extract of cocoa pod husk in PDN mice. The cocoa husk ethanol extract was formulated into emulgel and evaluated. Dermal sensitization reactions and a dermal acute toxicity test were conducted. In the PDN model, mice were induced using alloxan 225 mg/kg BW i. p. After 14 days, mice were randomized into eight groups: Normal, diabetic, 0.1% capsaicin cream, and cocoa pod husk extract emulgel (CPHEE) (0.25%, 0.5%, 1%, 2%, and 3%). Treatment was given three times a day for 14 days. Latency time and blood glucose levels were observed every week. Plantar skin sections were stained with h and e for histological observation and the transient receptor protein vanilloid (TRPV)-1 for immunohistochemistry. In vivo tests showed that a 2% dose of CPHEE improved hyperalgesia by 92.33% ±1.52%, improved histology, and minimized the expression of TRPV-1 in the skin, same as capsaicin 0.1%. Notably, up to a dose of 2000 mg/kg, CPHEE did not show toxic symptoms in mice or erythema and edema, further confirming its safety for use in PDN. The study confirms that a 2% CPHEE is effective and safe for topical use in PDN, providing a potential solution for patients suffering from this condition.